Alexander the Great, the Disguised Dinner Guest. Issue 1 (1st January 2018) - Garstad, Benjamin
Abstract : The Alexander Romance depicts Alexander going alone to the court of Darius disguised as his own messenger, dining with the Persians and advancing his own reputation as a munificent king. This episode substitutes a fictional scene for a number of dramatic banqueting incidents in the historical record that cast Alexander in a negative light, specifically, the burning of Persepolis, the proskynesis affair, and the wedding at Susa, which are all banqueting scenes concerned with Alexander's generosity, reputation, and relations with the Persians. It is also an opportunity for intertextual allusion, especially to Homer and Herodotus. It is, further, only one of many occasions in the Romance when Alexander is said to go alone to visit his enemies in disguise; these episodes integrate the composition and evince a concern with the treatment of ambassadors. It is finally one of the only instances of the explicit characterization of Alexander in the Romance .